2021
DOI: 10.1016/j.thromres.2021.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Suggestions for global coagulation assays for the assessment of COVID-19 associated hypercoagulability

Abstract: Introduction Severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) infection is associated with a clear prothrombotic phenotype. Although the exact pathophysiological mechanisms are not yet fully understood, thrombosis is clearly a highly important in the prognosis and outcome of COVID-19. As such, there is a need for diagnostic analysis and quantification of the coagulation potential in these patients, both at diagnosis and follow-up. Global coagulation assays like thrombin generation (TG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Sensitivity analyses excluding patients receiving ECMO during ICU admission did not alter any of the conclusions. Additionally, heparins execute limited effects on the ROTEM parameters; EXTEM and FIBTEM contain a heparin neutralizing agent (polybrene) and no clear fibrinolytic effect of heparins can be observed in tPA ROTEM (28). Taken together, the individualized treatment regimens, though illustrating the heterogeneous ICU population, do not in itself affect ROTEM results.…”
Section: Discussionmentioning
confidence: 98%
“…Sensitivity analyses excluding patients receiving ECMO during ICU admission did not alter any of the conclusions. Additionally, heparins execute limited effects on the ROTEM parameters; EXTEM and FIBTEM contain a heparin neutralizing agent (polybrene) and no clear fibrinolytic effect of heparins can be observed in tPA ROTEM (28). Taken together, the individualized treatment regimens, though illustrating the heterogeneous ICU population, do not in itself affect ROTEM results.…”
Section: Discussionmentioning
confidence: 98%
“…Of note, thrombin generation assays (TGAs) are highly sensitive to preanalytical aspects [119]. So far, some in vitro studies have reported that there was a heparin concentration dependent decrease in thrombin generation [120,121]. Studies showed that COVID-19 patients had a higher endogenous thrombin potential [31,39,48,66,[122][123][124][125][126][127]] than manufacturer's reference range, healthy controls or patients with sepsis, sometimes despite UFH or LMWH anticoagulation at a minimum of prophylactic dosing.…”
Section: Impact Of Differences In Anticoagulation Regimens (Type (Ufhmentioning
confidence: 99%
“…Unpublished data of patients using rivaroxaban and dabigatran show a concentrationdependent effect of these DOACs on tPA ROTEM CT, whereas tPA MCF, LOT, and LT were unaffected by DOAC concentration (data not shown). Similarly, heparins had no clear effect on tPA ROTEM parameters besides CT prolongation 16. Taken together, sis laboratory parameters and tPA ROTEM after COVID-19 ICU discharge and observed that, with the exception of tPA CT, values generally normalized over time.…”
mentioning
confidence: 75%
“…At 6-month follow-up, 32% of patients received anticoagulants, predominantly the direct oral anticoagulant (DOAC) apixaban (Table2). In vitro spiking studies demonstrated that LMWH, UFH, and DOACs prolong ROTEM CT 16,17. Unpublished data of patients using rivaroxaban and dabigatran show a concentrationdependent effect of these DOACs on tPA ROTEM CT, whereas tPA MCF, LOT, and LT were unaffected by DOAC concentration (data not shown).…”
mentioning
confidence: 93%